Basic Steffensen’s Method of Higher-Order Convergence - Ashour, Ola A. (International Journal of Advanced Engineering Research and Science, 2021)
In this paper, we introduce a new analog of a variant of Steffensen's method of fourth-order convergence for solving non-linear equations based on the q-deference operator.